Transesophageal Ultrasound Guidance for Endovascular Interventions on the Aorta - Castro-Verdes, Mireya; Yuan, Xun; Mitsis, Andreas; Li, Wei; Nienaber, Christoph A. (AORTA, 2022)
Aortic pathologies in general require a multidisciplinary approach and decision-making to integrate elements of clinical acuity, vascular pathology, individual comorbidity, and risk assessment; thus, ideally it is a center with access to multiple imaging modalities and expertise in all treatment options. Besides classic open surgical options, endovascular procedures have been accepted for a variety of aortic pathologies. More recently, novel transcatheter interventions even to the proximal aorta have been introduced, particularly for patients unfit for open surgery. Nevertheless, the role of transesophageal echocardiography to guide percutaneous aortic interventions is not well established, notwithstanding the growing potential as an ancillary tool to guide the procedure and document success.
Keywords: transesophageal echocardiogram; aorta; percutaneous intervention; aortic dissection; thoracic endovascular aortic repair